TA

Cho A = \(\dfrac{x+3}{\sqrt{x}+1}\)

Tính giá trị của biểu thức A khi \(x=9-4\sqrt{2}\)

NH
28 tháng 5 2023 lúc 14:49

A = \(\dfrac{x+3}{\sqrt{x}+1}\)\(x\) = 9 - 4\(\sqrt{2}\) 

Thay \(x\) = 9 - 4\(\sqrt{2}\) vào  biểu thức A = \(\dfrac{x+3}{\sqrt{x}+1}\) ta có:

A = \(\dfrac{9-4\sqrt{2}+3}{\sqrt{9-4\sqrt{2}}+1}\)  = \(\dfrac{12-4\sqrt{2}}{\sqrt{8-4\sqrt{2}+1}+1}\) 

A = \(\dfrac{12-4\sqrt{2}}{\sqrt{\left(2\sqrt{2}-1\right)^2}+1}\) = \(\dfrac{12-4\sqrt{2}}{2\sqrt{2}-1+1}\)

A = \(\dfrac{12-4\sqrt{2}}{2\sqrt{2}}\) = \(\dfrac{2\sqrt{2}\left(3\sqrt{2}-2\right)}{2\sqrt{2}}\)

A = 3\(\sqrt{2}\) - 2 

 

Bình luận (0)